Resistencia a antimicrobianos en aislamientos de Escherichia coli de origen animal - Carloni, G. (2011)
Antimicrobial susceptibility tests were determined in 100 isolates of E.coli from differents patologies in cattle, horses, dogs and cats, according to Clinical and Laboratory Standards Institute. Multiresistance isolates were detected in this assay. The antibiotics selected were amikacin, ampicillin /sulbactam, cefotaxime, ciprofloxacin, chloramphenicol, colistin, gentamicin, nitrofurantoin, streptomycin, tetracycline, trimethoprim/sulfamethoxazole. The antibiotic with the highest resistance was tetracycline (34% in cats and 75% in dogs). In isolated strains from dogs and cats it was also found considerable percentages of resistance to ampicilline/ sulbactam (27% in dogs and 53%in cats) and to ciprofloxacine (30%in dogs and 67% in cats). In these isolates it was also found the highest percentage of multiresistance (29% in dogs and 67% in cats). Selective pressure originated from the inadecuate use of antibiotics can be responsible for the appearance of resistance, eventhough it is not the only one. It may be possible that E. coli could transmit genes of resistance to antimicrobials agents, although it is unknown if the presence of these genes are permanent or transitory.